Strategi Kepemimpinan Ketua STIQ Dalam Pusaran Manajemen Pesantren - Hartono, Hartono (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2018)
Pesantren is one of the oldest Islamic education in the world because it has existed since the time of Prophet Muhammad Shallahu Alaihi Wasallam move or hijroh to Medina. His students were his friends of Muhajirin and taken care directly by Him using methods and manajamen in accordance with the development of Islam at that time. Now, the existence of pesantren popping up all over the world with their own styles and advantages. Under the auspices of these pesantrens in addition to religious education are also equipped with many institutions of formal education from basic to college as a balance between religious education with the needs of science. The leaders of these formal institutions are required to be able to adjust their educational institutions with the style that the pesantren caregivers want to show without having to change the order of management and pesantren culture. The appropriate strategy and leadership pattern will impact the out put graduates as the nation's future cadres.